Sustainable Culinary Business Model in the Industrial Era 5.0: A Case Study of Kapau Anak Sultan Medan Restaurant with Technology Integration and Green Economy: Model Bisnis Kuliner Berkelanjutan di Era Industri 5.0: Studi Kasus Restoran Kapau Anak Sultan Medan dengan Integrasi Teknologi dan Ekonomi Hijau - Steven; LISA ELIANTI NASUTION (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This research responds to the challenge of declining technological operational performance and low awareness of the green economy experienced by Kapau Anak Sultan Medan Restaurant in the midst of fierce competition in the culinary industry that increasingly relies on digital technology and environmental sustainability demands. This condition encourages the need to design an adaptive and environmentally friendly culinary business model in the transition period of modern industry that emphasizes collaboration between humans and technological sophistication as well as social environmental concerns. The research method used a quantitative approach by collecting data through questionnaires to loyal restaurant consumers and structural equation modeling analysis techniques based on PLS SEM to test the influence of technology integration and the application of the green economy on business sustainability. The results of the study confirm that the use of online ordering platforms connected to smart inventory systems, digitization of service processes, as well as sustainability practices such as strategic partnerships with local farmers, the use of renewable energy, and circular waste management systems make positive and significant contributions in strengthening operational efficiency, expanding market reach, increasing customer loyalty, and strengthening environmentally friendly brand image.